Creativity in early childhood teacher education: beliefs and practices - Ata-Akturk, Aysun; Sevimli-Celik, Serap (Informa UK Limited, 2020)
The aim of this study was twofold: (a) To carry out an in-depth investigation of pre-service teachers (PTs) beliefs regarding creativity and the perceived barriers of creative processes within earl...
Keywords: 4. Education